Fatty Liver Caused by Glycogen Storage Disease Type IX: A Small Series of Cases in Children - Leuzinger Dias, C. (2020)
Background: The prevalence of non-alcoholic fatty liver disease (NAFLD) affecting children and adolescents has increased dramatically in recent years. This increase is most probably related to the obesity pandemic and the high consumption of fructose. However, hepatic steatosis has some rare causes (e.g., some metabolic diseases) of which clinicians should be aware, particularly (but not only) when patients are non-obese or non-overweight. Differential diagnosis is notably important when pathologies have a specific treatment, such as for glycogenosis type IX (GSD-IX). Aims: To contribute to the knowledge on the differential diagnosis of NAFLD in paediatric age and to the clinical, biochemical, molecular, and histological characterisations of GSD-IX, a rare metabolic disorder. Methods: We performed a retrospective study of a small series of cases (n = 3) of GSD-IX diagnosed in the past 6 years, who were currently being followed up in the Units of Gastroenterology or Metabolic Diseases of the Paediatric Division of our hospital and whose clinical presentation was NAFLD in paediatric age. Results: Three male patients were diagnosed with NAFLD before 2 years of age, 2 with confirmed diagnosis before the age of 3 years (alanine aminotransferase [ALT], liver ultrasound, and molecular analysis) and 1 whose diagnosis was confirmed at 11 years (ALT, liver ultrasound, liver histology, and molecular analysis). None of the patients were obese or overweight, and the daily fructose consumption was unknown. The outcome was favourable in all 3 patients, with follow-up periods ranging from 2 to 6 years. Conclusion: The decision on how far the search for secondary causes of NAFLD should go can be difficult, and GSD-IX must be on the list of possible causes.